2004
DOI: 10.1002/eji.200324826
|View full text |Cite
|
Sign up to set email alerts
|

CREB function is required for normal thymic cellularity and post‐irradiation recovery

Abstract: Recent generation of genetically modified Creb1 mutant mice has revealed an important role for CREB (cAMP responsive element binding protein) and the related proteins CREM (cAMP responsive element modulator) and ATF1 (activating transcription factor 1) in cell survival, in agreement with previous studies using overexpression of dominant-negative CREB (dnCREB). CREB and ATF1 are abundantly expressed in T cells and are rapidly activated by phosphorylation when T cells are stimulated through the T cell antigen re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…This was surprising, as this is the first cell type in which we have found that the MAPK-dependent induction of these genes is independent of MSK-mediated CREB phosphorylation. Recently, a T cell-specific CREB knockout on an ATF1-null background was reported [46]. Consistent with our results, this report found no evidence in T cells for the involvement of CREB in the induction of several IE genes, including c-fos, in response to stimulation with PMA and ionomycin.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This was surprising, as this is the first cell type in which we have found that the MAPK-dependent induction of these genes is independent of MSK-mediated CREB phosphorylation. Recently, a T cell-specific CREB knockout on an ATF1-null background was reported [46]. Consistent with our results, this report found no evidence in T cells for the involvement of CREB in the induction of several IE genes, including c-fos, in response to stimulation with PMA and ionomycin.…”
Section: Discussionsupporting
confidence: 88%
“…Total CREBknockout mice, which die shortly after birth, were reported to have an impaired transition from DN to DP cells and reduced TCRb expression in the embryonic thymus [50]; it is unclear whether this was due to a primary defect in the T cells or a deficiency in stromal support. However, analysis of a T cell-specific CREB/ total ATF1-knockout demonstrated that CREB is not essential for T cell development, but a reduced number of thymocytes were observed in the mice [46]. Overexpression of a CREB Ser133Ala mutation also resulted in decreased thymocyte proliferation; however, these mice exhibited additional phenotypes, such as reduced gene induction and increased apoptosis, compared to the CREB-knockout mice [28].…”
Section: Discussionmentioning
confidence: 96%
“…This finding was somewhat unexpected because a recent analysis of mice in which CREB and ATF-1 had been deleted selectively in T cells showed IL-4 expression to be preserved (31). However, a significant proportion of spleen and lymph node T cells (24 and 12%, respectively) in the knock-out mice still expressed CREB, raising the possibility that residual CREB activity was sufficient to support IL4 mRNA expression in that experimental model.…”
Section: Discussionmentioning
confidence: 47%
“…After searching in the PubMed, we came to know the key roles of each protein and its possible relationship with immunity or dendritic cells. We classified the proteins into 7 categories, including cell division, cell signaling or communications, cell structure or motility, cell or organism defense, gene or protein expression, metabolism, and unclassified [26][27][28][29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…To avoid the decrease in PCR volume and keep the same amount of PCR volume in each Eppendorf tube, mineral oil was added. For semi-quantitative PCR, 4 different cycles were amplified for the 4 tubes (18,23,28,33) to compare the PCR yield. The forward primer of G3PDH is CTC CCA CTC TTC CAC CTT CGA TGC, and the reverse primer is CCT CTC TTG CTC AGT GTC CTT GCT (Supporting data, Table S1).…”
Section: Rt-pcr and Semi-quantitative Rt-pcrmentioning
confidence: 99%